Survey Design and the Analysis of Satisfaction - Conti, Gabriella; Pudney, Stephen (The Review of Economics and Statistics, 2011)
We analyze the effect of survey design on reported job satisfaction by exploiting two quasi-experiments in the British Household Panel Survey: a change in question design and parallel use of different interview modes. We show that apparently minor differences in survey design lead to substantial biases in econometric results, particularly on gender differences. The common empirical finding that women care less about wages and prefer to work fewer hours than men appears largely an artifact of survey design rather than a true behavioral difference.